AN ERROR ANALYSIS OF COMPOSITION WRITTEN BY ENGLISH DEPARTMENT STUDENTS OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA - MUFIDAH, ROHMATUL (2011)
This study aims at describing the types of errors written by first grade of English Department students of Muhammadiyah University of Surakarta, describing the frequency of its type of errors, and explaining the sources of errors. The type of this research is descriptive qualitative research. In collecting the data, the writer uses documentation method by selecting the errors which are written by first grade students. The steps for collecting the data are finding students’ composition test with the topic given, reading and marking types of error in the student’s work, writing the erroneous sentences. The collected data are analyzed by using Dulay, Burt, and Krashen classification of errors theory, Slamet the frequency of type of error theory and Brown source of errors theory. The results of the research show that the first grade of English department students of Muhammadiyah University of Surakarta still make 188 errors in their compositions. The writer finds that from the 188 data, there are ten classifications of error based on the combination of linguistic category and surface strategy taxonomy. They are TO BE (20, 74%), verb 20, 74%, bound morpheme -s/ -es 18, 09%, vocabulary 13, 30%, noun 12, 23%, grammatical structure 6, 92%, preposition 3, 73%, article 2, 13 %, conjunction 1, 06%, and adjective 1, 06%.It is derived from 36 types of error. The highest frequency of errors that the researcher found are TOBE errors and verb errors. There are 39 or 20, 74% errors that the writer found from the total errors. The researcher also finds 2 dominant sources of error, namely: interlingual transfer and intralingual transfer.